2017
DOI: 10.1111/jfs.12363
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, antimicrobial resistance, toxin gene profiles, and toxin production ability of Bacillus cereus isolates from doenjang, a Korean fermented soybean paste

Abstract: The objectives of this study were to determine the toxin gene profile, toxin production, and antibiotic resistance of Bacillus cereus isolates from doenjang, a Korean fermented soybean paste. Repetitive element sequence polymorphism‐PCR (rep‐PCR) was also used to assess the genetic diversity between these isolates. Thirty‐five B. cereus strains were isolated from 67 commercial doenjang samples, and all 35 isolates carried the nheABC and entFM genes and produced NHE enterotoxin. Of them, 12 strains harbored the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
(46 reference statements)
6
11
0
Order By: Relevance
“…Toxigenic characterization of the isolates by mPCR showed that the nhe operon was present in all isolates, entFM gene in 92.9% of isolates, cytK2 gene in 24.1%, hblCDAB in 28.6%, hblCDA in 29.5%, and hblA in one isolate (0.9%); isolates carrying cesB gene were not identified. Similar to these results, a large distribution of toxin genes is observed in other countries all over the world such as Korea, Latvia, and Canada, with the enterotoxin genes (particularly, nhe operon and entFM) present in higher frequencies, and the emetic toxin genes were not detected (Lee et al, 2017;Saleh-Lakha et al, 2017;Fogele et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Toxigenic characterization of the isolates by mPCR showed that the nhe operon was present in all isolates, entFM gene in 92.9% of isolates, cytK2 gene in 24.1%, hblCDAB in 28.6%, hblCDA in 29.5%, and hblA in one isolate (0.9%); isolates carrying cesB gene were not identified. Similar to these results, a large distribution of toxin genes is observed in other countries all over the world such as Korea, Latvia, and Canada, with the enterotoxin genes (particularly, nhe operon and entFM) present in higher frequencies, and the emetic toxin genes were not detected (Lee et al, 2017;Saleh-Lakha et al, 2017;Fogele et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…None of the isolates carried cesB gene, therefore, they were not able to produce the emetic toxin. This is a frequent finding (Altayar and Sutherland, 2006) with few exceptions of studies that have found B. cereus emetic strains in various foods (López et al, 2015;Park et al, 2016;Lee et al, 2017;Lin et al, 2017;Mudagza and Buys, 2017;Yang et al, 2017;Frentzel et al, 2018). In Colombia, the cesB gene was detected in DNA directly extracted from cassava starch (Sánchez et al, 2014); however, there are no reports about isolated emetic strains.…”
Section: Discussionmentioning
confidence: 99%
“…CytK is a cytotoxin isolated from a B. cereus strain that caused a severe food poisoning outbreak leading to three deaths in France (Lund et al, 2000). The cytK gene was present in 68% of the B. cereus isolates identified in this study, consistent with earlier studies that found the gene in 40-73% of B. cereus strains isolated from foods (Hwang and Park, 2015;Lee et al, 2017;Gao et al, 2018). Hence, the widespread distribution of diarrheacausing B. cereus in RTE foods and its potential hazards cannot be ignored.…”
Section: Virulence Gene Profiles Of B Cereus Isolatessupporting
confidence: 88%
“…Detection of nheA, nheB, nheC, hblA, hblB and hblC genes is useful to verify the potential to cause diarrheal illness in strains belonging to B. cereus group (Ehling-Schulz et al, 2004). According to Lee et al (2017), from 90% to 100% from B. cereus group isolated from food samples can carry the hblACD and nheABC genes. Chaves et al (2011) evaluated 97 strains of B. cereus sensu stricto collected over three years and observed that 84.5% and 62.9% of the strains were positive for NHE and HBL complex, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…On the work of Lee et al (2017), only 8.6-23% of the isolates containing hbl encoded the enterotoxin HBL. The production of hemolytic and nonhemolytic enterotoxins is complex and involves transcriptional regulator proteins, posttranscriptional and posttranslational regulatory mechanisms and environmental conditions (Jeßberger et al, 2015).…”
Section: Discussionmentioning
confidence: 99%